2016
DOI: 10.1039/c5md00392j
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of levofloxacin – M33 peptide conjugation or combination

Abstract: M33 is a branched antimicrobial peptide against Gram-negative bacteria. We reported its conjugation with levofloxacin and its antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…The M33 tetra-branched peptide, designed and optimised from an E. coli phage library, acts complementary to levofloxacin against E. coli and P. aeruginosa; however, its conjugation to levofloxacin did not substantially increase the activity of M33 alone [113]. A further study demonstrated that M33's activity extends to AG, CP, PC, and RF classes against A. baumannii and K. pneumoniae [114].…”
Section: De Novo Hdpsmentioning
confidence: 95%
“…The M33 tetra-branched peptide, designed and optimised from an E. coli phage library, acts complementary to levofloxacin against E. coli and P. aeruginosa; however, its conjugation to levofloxacin did not substantially increase the activity of M33 alone [113]. A further study demonstrated that M33's activity extends to AG, CP, PC, and RF classes against A. baumannii and K. pneumoniae [114].…”
Section: De Novo Hdpsmentioning
confidence: 95%
“…Зниження афінності виникає в результаті спонтанних мутацій, які призводять до амінокислотних замін в ділянках поліпептидних ланцюгів ДНК-гірази чи топоізомерази IV, що входять до складу "хінолонової кишені". У ході проведених досліджень встановлено, що ДНК-гіраза грампозитивних бактерій, на відміну від грамнегативних, менш чутлива до інгібуючого впливу фторхінолонів, а основною мішенню препаратів у грампозитивних мікроорганізмів є топоізомераза IV [5]. У дослідженні Boselli E. та співавт.…”
Section: механізми дії та резистентностіunclassified
“…The conjugate magainin II-vancomycin demonstrated higher activity against vancomycin-resistant Enterococci compared to vancomycin alone [ 139 ]. Other peptides such as M33, indolicidine, or transactivating transcriptional activator (TAT) have been conjugated with levofloxacin for POT [ 140 ]. M33 is a branched synthetic peptide with a broad-spectrum antibacterial effect by binding lipopolysaccharide (LPS) on the surface of Gram-negative bacteria [ 141 ].…”
Section: Antimicrobial Peptides (Amps) In Combatting Amrmentioning
confidence: 99%